Excited states engineering enables efficient near-infrared lasing in nanographenes. Issue 1 (4th October 2021) - Paternò, Giuseppe M.; Chen, Qiang; Muñoz-Mármol, Rafael; Guizzardi, Michele; Bonal, Víctor; Kabe, Ryota; Barker, Alexander J.; Boj, Pedro G.; Chatterjee, Shreyam; Ie, Yutaka; Villalvilla, José M.; Quintana, José A.; et al.
Abstract : Organic molecules usually exhibit optical gain losses in the NIR, due to the absorption of charged species/triplets. We report on a nanographene molecule in which the minimisation of such losses enable the achievement of low-threshold NIR lasing. Abstract : The spectral overlap between stimulated emission (SE) and absorption from dark states ( i.e. charges and triplets) especially in the near-infrared (NIR), represents one of the most effective gain loss channels in organic semiconductors. Recently, bottom-up synthesis of atomically precise graphene nanostructures, or nanographenes (NGs), has opened a new route for the development of environmentally and chemically stable materials with optical gain properties. However, also in this case, the interplay between gain and absorption losses has hindered the attainment of efficient lasing action in the NIR. Here, we demonstrate that the introduction of two fluoranthene imide groups to the NG core leads to a more red-shifted emission than the precursor NG molecule (685 vs. 615 nm) and also with a larger Stokes shift (45 nm vs. 2 nm, 1026 cm −1 vs. 53 cm −1, respectively). Photophysical results indicate that, besides the minimisation of ground state absorption losses, such substitution permits to suppress the detrimental excited state absorption in the NIR, which likely arises from a dark state with charge-transfer character and triplets. This has enabled NIR lasing (720 nm) from all-solution processed distributed feedback devices with one order of magnitude lower thresholds than those of previously reported NIR-emitting NGs. This study represents an advance in the field of NGs and, in general, organic semiconductor photonics, towards the development of cheap and stable NIR lasers.